Technical papers of 1986 ACSM-ASPRS annual convention - ACSM-ASPRS Annual Convention (1986 : Washington D. C.); American Congress on Surveying and Mapping; American Society for Photogrammetry and Remote Sensing
Vol. 1. Cartography and education -- vol. 2. Surveying, instrumentation, and the global positioning system -- vol. 3. Geographic information systems -- vol. 4. Photogrammetry -- vol. 5. Remote sensing